Menelisik Legalitas Ahli untuk Mengundurkan Diri atau Minta Dibebaskan dari Kewajiban Memberikan Keterangan di Persidangan - Erwin Susilo; Muhammad Rafi; Khairul Umam Syamsuyar (Jurnal Interpretasi Hukum, 2024)
Article 168 of Indonesian Criminal Procedure Code (KUHAP) confers upon witnesses’ right to decline provide testimony, while Article 170 (1) stipulates that a witness may seek exemption from the obligation to testify. However, these provisions do not extend to experts, despite their frequent application in trials. This study seeks to critically analyze the role of experts in criminal evidence law and their legal standing to either withdraw or request exemption to testify. Employing a normative legal research method, the study reveals the following insights: First, experts are instrumental in elucidating non-legal aspects that are beyond the understanding of judges and parties in court, utilizing their specialized knowledge. However, they should refrain from making final conclusions, as this responsibility lies exclusively with the judge. Second, witnesses are required to provide objective testimony and may face penalties for perjury (pursuant to Article 242 KUHAP, Articles 291, and 373 of Law No. 1 of 2023), whereas experts offer subjective opinions and are not subject to such penalties. Consequently, Article 168 KUHAP is applicable solely to witnesses, while Article 170 KUHAP, through systematic interpretation linked with Article 120 (2) KUHAP, can be extended to encompass both witnesses and experts. The study advocates for the reformulation of Article 170 (1) KUHAP to explicitly include experts as individuals who may seek exemption from the obligation to testify, thereby safeguarding professions that are bound by confidentiality obligations.